Therapies to prevent post-infarction remodelling: From repair to regeneration. (August 2021) - Contessotto, Paolo; Pandit, Abhay
Abstract: Myocardial infarction is the first cause of worldwide mortality, with an increasing incidence also reported in developing countries. Over the past decades, preclinical research and clinical trials continually tested the efficacy of cellular and acellular-based treatments. However, none of them resulted in a drug or device currently used in combination with either percutaneous coronary intervention or coronary artery bypass graft. Inflammatory, proliferation and remodelling phases follow the ischaemic event in the myocardial tissue. Only recently, single-cell sequencing analyses provided insights into the specific cell populations which determine the final fibrotic deposition in the affected region. In this review, ischaemia, inflammation, fibrosis, angiogenesis, cellular stress and fundamental cellular and molecular components are evaluated as therapeutic targets. Given the emerging evidence of biomaterial-based systems, the increasing use of injectable hydrogels/scaffolds and epicardial patches is reported both as acellular and cellularised/functionalised treatments. Since several variables influence the outcome of any experimented treatment, we return to the pathological basis with an unbiased view towards any specific process or cellular component. Thus, by evaluating the benefits and limitations of the approaches based on these targets, the reader can weigh the rationale of each of the strategies that reached the clinical trials stage. As recent studies focused on the relevance of the extracellular matrix in modulating ischaemic remodelling and enhancing myocardial regeneration, we aim to portray current trends in the field with this review. Finally, approaches towards feasible translational studies that are as yet unexplored are also suggested.